Using life histories to explore gendered experiences of conflict in Gulu District, northern Uganda: Implications for post-conflict health reconstruction - Ssali, Sarah N.; Theobald, Sally (South African Review of Sociology, 2016)
The dearth of knowledge about what life was like for different women and men, communities and institutions during conflict has caused many post-conflict developers to undertake reconstruction using standardized models that may not always reflect the realities of the affected populations. There is a need to engage with and understand the life experiences, transformations and social concerns of people affected by conflict before, during and after the conflict in order to develop appropriate and context embedded post-conflict reconstruction strategies. This article discusses how life histories were deployed to explore how the 20 year conflict in northern Uganda transformed people’s lives. It presents how 47 men and women lived, experienced and remembered the war in northern Uganda, and the implications for health care reconstruction
Keywords: Uganda; Conflict; Life histories; Gender; Health